Strategi Pengembangan Fasilitas Umum di Daya Tarik Wisata Solok Radjo Aia Dingin Kabupaten Solok - Aulia Ilham; Yuliana Yuliana (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
The problem in this research is that there are inadequate toilets at the Solok Radjo Tourist Attraction, because there are only two public toilets at this Tourist Attraction. The prayer room is still made of wood and can only accommodate 2-5 people in worship. Insufficient number of rubbish bins at the Solok Radjo Tourist Attraction. There is no special parking area that is neat and well arranged at the Solok Radjo Tourist Attraction. This type of research is a type of descriptive research with qualitative data. This research was conducted at the Solok Radjo Aia Winter Tourist Attraction, Solok Regency, and data collection will be carried out in October-November 2022. The results of this research are 1) Internal factors that become strengths and weaknesses in the development of public facilities In the Solok Radjo Aia Winter tourist attraction, Solok Regency, the strength is that public toilets which are used by visitors for urinating, defecating and performing ablution are very available, where the Solok Radjo Aia Winter tourist attraction has 12 public toilets. Apart from that, the parking area is large so it can accommodate many vehicles, both motorbikes and cars. Meanwhile, the weakness is that the prayer room is only made of wood with a tarpaulin, mat and this is the place used by visitors for prayer. The next weakness is that the rubbish bins around the tourist attraction location are limited, namely only 5 rubbish bins. 2) External factors that become opportunities (Opportunities) and threats (Threats) regarding public facilities at the Solok Radjo Aia Winter Tourist Attraction, Solok Regency, namely the opportunity (Opportunities) is the construction of a Mushalla/Mosque with magnificent architecture which has the opportunity to develop religious tourism. Furthermore, the opportunity (Opportunities) is the cleanliness of tourist locations which can be realized through the availability of organic and non-organic rubbish bins at every point in the Solok Radjo Aia Winter tourist attraction area, Solok Regency. Meanwhile, the threat is the number of visitors who lose their items or have items scattered in the public toilets at the Solok Radjo Aia Winter tourist attraction. Furthermore, another threat is the parking lot which is sometimes frequented by many thugs.